STAKEHOLDER INTERESTED ORIENTATION IN TRADITIONAL MARKET REVITALIZATION POLICIES IN SITUBONDO DISTRICT - Fauzi, Hasan Muchtar; Hasanah, Usrotul (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
Regional Governments are given the authority to revitalize traditional markets in accordance with the needs in order to be competitive and improve the welfare of traders. However, the programmed revitalization did not run optimally, due to differences in the orientation of the interests of stakeholders who were not properly organized, causing dissatisfaction with certain groups. The research objective is to describe the orientation of stakeholders in the involvement of traditional market revitalization policies in Situbondo Regency. The method used is descriptive qualitative phenomenological approach. Research locus of Sumberkolak market, Panarukan market and Besuki market. The research analysis unit for stakeholders with an interest in traditional market revitalization policies is, first, Inside Local Government; DPRD, Diskoperindag, Executive, UPTD, DPKD. Second, Inside Local Government Participant; Bappeda, DTKP, DLHK, BPS, Private. Third, Outside Local Government; Traders, Cultural Leaders, NGOs. Fourth, Outside Local Government Participant; Traditional market consumers, Society. The research findings show that there are three dominant interests, (1), traders are oriented towards increasing income, (2), local government is oriented towards increasing PAD, (3), cultural figures are oriented towards religious cultural values ​​that are integrated into activities in the market . From this orientation of interests, market traders are neglected, giving rise to dissatisfaction pros and cons that are considered not to be on their side. It is necessary to involve all stakeholders who have a direct interest in revitalization without ignoring the interests of one group, so that the policies implemented are fair